Surgical Management of Buccal and Palatal Impacted Canines: A Two-Case Report - Arshiya, Arshiya; Sood, Anchal; Chaudhry, Swantika; Khichy, Aditya; Kaur, Arshdeep (Journal of Neonatal Surgery, 2025)
Maxillary canine impaction is a common dental anomaly that affects esthetics, occlusion, and periodontal health. Palatal impactions are more frequent than buccal ones, with a 2:1 female predilection. If left untreated, impacted canines may cause root resorption, cyst formation, and malocclusion. Early diagnosis and intervention are essential for optimal outcomes. This report presents two cases: a palatally impacted canine and a labially impacted canine, managed using an open window technique, allowing direct visualization and orthodontic guidance. Both procedures were performed under local anesthesia, with orthodontic brackets and traction chains bonded to guide eruption. Postoperative healing was uneventful, with no signs of infection or root resorption. Surgical exposure combined with orthodontic traction is an effective treatment approach, ensuring functional and esthetic outcomes when managed through a multidisciplinary strategy.